Morphometric characteristics of Wadi Kadira Al-Adhabi Basin in Al-Zubair District, southwestern Iraq - Ghalib Majeed, Researcher .Masara; Abdel-Amir Rashm Al-Asadi , Prof. Dr. Safaa; Gomaa Ali Al-Mawla, Prof. Dr. Tariq (Basra studies journal, 2026)
The research dealt with the most important morphological characteristics and their hydrological implications for the Wadi Kaderah Al-Adhabi basin in southwestern Iraq, one of the seasonal valleys of a region in a governorate within the administrative borders of the Basra and Dhi Qar governorates. It flows in a north-south direction, with an area of ​​(1022.22) km2, a length of (71.19) km, and a width of ( 9.99 km with a circumference of (249.38) km, where the most important natural factors such as geological structure, surface, climate, and water resources influencing the formation of the morphological characteristics of the Wadi Kadirah Al-Ajabi Basin were studied. The morphometric characteristics of the main basin and its secondary basins were studied by analyzing the cadastral characteristics and basin dimensions of the region using ArcGIS 10.8, and accessing a set of tools and capabilities to analyze geographic data accurately and comprehensively. The formal morphometric indicators of the pelvis were analysed, such as roundness, elongation, pelvic shape factor, and circumference cohesion ratio. The roundness ratio reached (0.23), and this indicates that the pelvis is close to a rectangular shape. The elongation ratio was (0.50), while the value of the basin shape factor was (0.20) and the ocean cohesion ratio was (2.67), which provides a deeper understanding of the factors affecting the basin’s hydrological system and allows for the design of effective strategies to manage water resources in a more sustainable and efficient manner.